Penyimpangan Moral dan Kepercayaan Publik Studi tentang Perselingkuhan Aparatur Sipil Negara di Indonesia - Nugraha, Irwan Abdu; MIDHOL, AHMAD BAIHAQI (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2025)
This research aims to examine the phenomenon of infidelity among Civil Servants through the perspective of social role theory that emphasizes the influence of norms, social expectations, and sanctions on individual behavior. Civil Servants infidelity not only reflects individual moral deviations but also has serious repercussions on the image and integrity of government institutions. This study employs a qualitative approach with literature analysis, online news content analysis, and review of regulations such as Government Regulation Number 94 of 2021 concerning the Discipline of Civil Servants. The results indicate that cases of Civil Servants infidelity undermine public trust and have significant social and professional consequences. Although regulations have explicitly outlined sanctions, their implementation in the field still faces various challenges, including inconsistencies in law enforcement and organizational cultural resistance. This study emphasizes the importance of enforcing social norms and maintaining an integrity-driven bureaucracy to uphold public trust in civil servants.